Energy Consumption and Environmental Aspects of Drying Processes - Sniezhkin, Yu.; Petrova, Zh. (Science and Innovation, 2023)
Introduction. Energy saving and environment protection are global problems. The energy capacity of world production is growing faster than the industry’s output. Currently, the world has been experiencing a shortage of energy, while environmental pollution has been increasing, as the industrial load on the environment has grown several times in recent years. Therefore, energy resource saving and environment protection have been becoming more and more important. Problem Statement. Drying belongs to complex energy-intensive processes. Industries that use drying processes consume significant energy resources. The use of outdated drying equipment and imperfect technological processes contributes to the energy resources consumption and environment pollution with vapor that is part of greenhouse gases. Therefore, it is urgent to find ways to reduce these adverse consequences. Purpose. The purpose of this research is to identify and to analyze the trends in reducing energy consumption and hazardous vapor emissions in the drying processes. Material and Methods. Analytical and practical methods, comparative analytical and systemic approaches have been employed. Scholarly research works and developments of Ukrainian researchers in the field of study have been used as materials. Results. The main methods of saving energy and reducing vapor emissions in drying processes have been summarized. The developments of Ukrainian researchers of the Institute of Engineering Thermophysics of the National Academy of Sciences of Ukraine have made it possible to obtain a significant energy saving that is estimated at 2.0—2.1 million tons of conventional fuel, and to reduce environmentally hazardous vapor emissions by at least 4 million tons per year. Conclusions. The creation and implementation of new energy-efficient and environmentally safe equipment and technologies allows not only reducing energy consumption and emissions of dangerous vapor into the environment, but also optimizing the use of raw materials and obtaining high-quality products in drying processes.